Studi Desentralisasi dan Otonomi Daerah Analisis Pemekaran Daerah Otonomi di Indonesia Dalam Perspektif Undang Undang Nomor 23 Tahun 2014 untuk menciptakan pelayanan yang baik. - MUHAIMIN; Hakim, Lukman; Dharmawan, Awan (Universitas Teknologi Surabaya, 2024)
Regional development is usually a manifestation of the desire of the people in a region to grow and develop in the economic, political, social, cultural and security fields, in geographical dimensions. The level of regional development can be seen from the ratio of the built-up area to the total area. The greater the ratio, the higher the level of regional development. Regional expansion, or rather dividing an autonomous region into several regions, aims to bring closer and optimize government services to the community, accelerate development growth in order to improve the welfare of the people in the area. Regional expansion is a phenomenon that accompanies the implementation of regional government in Indonesia. This can be seen from the increase in the number of New Autonomous Regions (hereinafter referred to as DOBs) in the territory of the Unitary State of the Republic of Indonesia (hereinafter referred to as the Republic of Indonesia) during 2003 to 2022, there are 511 new autonomous regions, and currently Indonesia has 542 autonomous regions consisting of 38 provinces, 415 districts and 97 cities. The presence of Law Number 23 of 2014 concerning Regional Government (hereinafter referred to as Law No. 23 of 2014), regional autonomy which is expected to be able to improve services and welfare for the community. The provision of public services is aimed at creating community welfare. Public service is defined by Sinambela as